Hubungan Aktivitas Fisik dan Stres Dengan Kejadian Hipertensi Pada Lanjut Usia di Wilayah Kerja Puskesmas Sukabumi - Arifuddin Arifuddin; Burhanuddin Basri (Cindoku : Jurnal Keperawatan dan Ilmu Kesehatan, 2024)
Hypertension is a disease that can affect anyone, both young and old. Increased blood pressure caused by less physical activity will cause complications such as heart disease, and prolonged stress can increase blood pressure to stay high. To determine the relation of physical activity and stress with the incidence of hypertension in the elderly in Tete Community Health Center work area of Tojo Una-Una Regency. This research uses descriptive correlation method with a cross-sectional approach and uses the Mann-Whitney U test. The population in this research were elderly who were in the 5 villages of the Tete Community Health Centre of Tojo Una-Una Regency. The number of samples in this research were 112 respondents who were taken using the proportional random sampling technique. There is a relation between leisure activities and total PASE with the incidence of hypertension (<0,05). There is no relation between household activity, and work activity with the incidence of hypertension (>0,05). There is a relation between stress with the incidence of hypertension in the elderly (<0,05). For people in the working area of the Tete Community Health Centre, it is recommended to prevent as early as possible the occurrence of hypertension, especially people who have risk factors for hypertension through improved lifestyles, adequate physical activity, stress control, and the need for blood pressure checks, routine treatment, and lead a healthy lifestyle.